Isoflavone and triterpenoid isolated from an endemic plant Genista microcephala Coss et Dur. - Ilhem Bouakaz; Leila Beggour; Ammar Dibi; Georges Massiot; Hamada Haba (GarVal Editorial Ltda., 2015)
Context: Genista microcephala Coss et Dur is a plant that grows in northern of Algeria. The Genista species show interesting biological properties. Aims: To study phytochemically of the aerial parts of G. microcephala and search new compounds with pharmacological interest. Methods: Aerial parts of G. microcephala were extracted using chloroform. The extract was purified by several chromatography processes. Isolated compounds were analyzed by the usual spectroscopic methods and 2D NMR technics. Results: From the chloroformic extract of the air parts of Genista microcephala (Leguminosae) two known components were obtained. The structures of these compounds were oleanolic acid (1), alpinum isoflavone (2) elucidated by the usual spectroscopic methods and 2D NMR technics and by comparison with literature data. Conclusions: Two known components were obtained from the chloroformic extract of the air parts of Genista microcephala but they have not previously been reported from this species.